Validity and Reliability of The Arabic Version of De Morton Mobility Index after Abdominal Surgeries: A Cross-Sectional Study - A. Younes, Basant; M. Othman, Eman; M. Nabeeh, Dina; Abouzid, Amr; I. Saafan, Karim (Journal of Neonatal Surgery, 2025)
Background: Post-abdominal surgery patients often experience decreased mobility, which necessitates precise evaluation tools. The De Morton Mobility Index (DEMMI) is a well-regarded scale for assessing various aspects of mobility. Although validated in several languages, no Arabic version has been reported to date. Purpose: This study aimed to validate and determine the reliability of the Arabic-translated version of DEMMI for Egyptian patients who had undergone abdominal surgeries. Methods: The study was carried out in the following two major steps: The first step involved translating the DEMMI from English to Arabic, looking at both forward and backward translations. Experts thoroughly examined the finalized version to determine its authenticity and the accuracy of its face and content validity. Step 2: Following abdominal procedures, 103 patients of both sexes (62 females and 41 males) had the scale’s psychometric properties evaluated. They were between forty and sixty years old. The feasibility of the scale was assessed based on the time required to finish it. The reliability was further evaluated using test-retest reliability and internal consistency. In addition to filling out the index, patients were requested to return it 24 hours later to ensure its test–retest reliability. Results: The Arabic DEMMI demonstrated exceptional face validity, with a clarity index of 96.76% and an average response clarity of 90%. Content validity was high, with an S-CVI value of 0.98. Reliability testing indicated Cronbach’s alpha of 0.903, signifying excellent internal consistency. Test-retest reliability was robust, with the overall Intraclass Correlation Coefficient (ICC) at 0.968 (95% CI: 0.953–0.979). Conclusion: The Arabic DEMMI is a reliable, valid, and user-friendly instrument for assessing mobility impairments in patients recovering from abdominal surgeries.